2020
DOI: 10.1186/s12876-020-01285-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transendoscopic tube-delivered enteral therapy (with video): a prospective study

Abstract: Background Colonic transendoscopic enteral tubing (TET) refers to colonic transendoscopic tube-delivered enteral therapy. Colonic TET has been successfully used for frequent colonic administration of drugs or multiple fecal microbiota transplantations (FMTs). This prospective observational study aimed to evaluate possible factors affecting methodology, feasibility and safety of colonic TET. Methods Patients who underwent colonic TET at our center from October 2014 to November 2018 were included. The feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…Drug infusion is facilitated by colonoscopy while minimizing psychological discomfort, but bowel preparation can be found unbearable by some patients [28]. The Transendoscopic enteral tubing(TET) route has also been proposed as a solution to the limitations of repeated FMT in a short period of time, avoiding intestinal injury and bleeding caused by repeated insertion of enema tubes or colonoscopy [23,29]. Nevertheless, only 5.81% of patients in our study chose the TET, due to the low awareness of TET in patients with IBD .…”
Section: Discussionmentioning
confidence: 99%
“…Drug infusion is facilitated by colonoscopy while minimizing psychological discomfort, but bowel preparation can be found unbearable by some patients [28]. The Transendoscopic enteral tubing(TET) route has also been proposed as a solution to the limitations of repeated FMT in a short period of time, avoiding intestinal injury and bleeding caused by repeated insertion of enema tubes or colonoscopy [23,29]. Nevertheless, only 5.81% of patients in our study chose the TET, due to the low awareness of TET in patients with IBD .…”
Section: Discussionmentioning
confidence: 99%
“…Youngster 等人 [74] 首次报道使用口服冻存粪菌溶液制成的胶囊来治疗复发性难辨 梭状芽孢杆菌感染,腹泻症状的临床缓解达到 90%。甚至近年来用于治疗肝性脑 病的Ⅰ期临床试验也证实了此种给入途径的有效性与安全性 [20] 。 口服途径给药方 便(除外吞咽功能异常患者)、可重复且易为患者接受,但在不同的疾病中其疗 效不稳定且无治疗的参照标准。 由于内镜技术的不足或其他原因限制而人为提高 粪菌胶囊使用率,会在一定程度上带来降低临床疗效的风险。2018 年发表在 Gut 上的一项关于运用粪菌胶囊治疗肠易激综合征的随机双盲对照试验显示 [75] , 口服 胶囊的治疗对患者症状的长期改善作用与安慰剂组相比并无显著差异。 而另一项 针对 FMT 改善肥胖患者代谢水平的随机双盲对照试验结果也显示 [25] ,口服胶囊 的治疗组的体重和大部分代谢指标与安慰剂组相比均未得到显著改善。 由此可见, 全球的临床试验中, 有部分研究取得阴性结果的原因可能是由于研究者盲目把粪 菌胶囊治疗难辨梭状芽胞杆菌感染的疗效等同于可以治疗其他疾病。 鼻胃管途径的给入则具有操作简便、留置时间长可供重复移植、可同时鼻饲 营养液的优点,但也存在如下缺点:较易引起鼻咽部不适;导管易滑脱;菌液接 触胃酸可能失活等。因此在临床实践中,推荐鼻胃管作为无法通过其他途径移植 的候选途径,如呼吸道传染性疾病合并肠道感染需要实施 WMT 的患者 [71] 。因为 对于这类患者,使用一些传统的移植途径例如灌肠是不合适的,频繁的咳嗽通常 会导致粪菌悬液难以在体内保留较长的时间。而如果采取内镜下治疗的方式,则 更容易增加飞沫或分泌物等传播呼吸道疾病的风险 [71] [78] 。在输注菌液的过程中,为提高适应性患者应对整个治疗过程不 可见。 应警惕移植途径相关不良事件, 如吸入性肺炎这一严重不良事件可能与移植 途径有关,经胃镜输送菌液至十二指肠 [79.80] 或经结肠镜输送菌液至结肠 [81] 的操作 都有报道发生移植相关的致命性吸入性肺炎。相应措施可以降低误吸概率:床头 抬高 10 度并保持 30 分钟防止菌液返流; 单次给入的治疗剂量在 7 岁以下幼儿和 7 岁以上儿童和成人中的范围是 10-50 mL,输注速度保持为 50 mL/1-2 min [10] ; 移植前应用促胃动力药胃复安可显著缩短内镜下的输注时间, 并降低菌液从十二 指肠远端返流到胃内的发生率 [77] 。 2.3 下消化道途径 下消化道途径主要包括灌肠、结肠镜、结肠造瘘口、以及结肠 TET 等。灌 肠途径已被应用于复发性难辨梭状芽孢杆菌感染患者 [82,83] ,儿童 [84] 及危重患者 [85] 。 当无条件选择其他移植途径时,可考虑操作简便、可重复的灌肠途径,尤其是对 于病变局限于直肠、乙状结肠的患者,灌肠途径可直接作用于病变部位,但也存 在难以到达结肠等深部病变位置的弊端。最近的一项 Meta 分析表明,通过灌肠 给入菌群治疗难辨梭状芽孢杆菌感染的疗效低于结肠镜途径 [86] 。 结肠镜途径虽可 试验表明透明帽辅助可明显缩短结肠 TET 植管第二次进镜时间,尤其是针对便 秘等实施肠镜较困难的病人优势尤为明显 [87] 。结肠 TET 具有给药、取样和引流的 作用。 结肠 TET 途径的菌群移植价值和方法,已被 Gut 和 Chinese Medical Journal 所发表的指南或共识推荐 [31,88] 。2016 年,关于使用结肠 TET 行 FMT 治疗的前 瞻性观察研究显示 [70] , 结肠 TET 的操作成功率为 100%, 获得了 98.1% 的满意度, 并且在植管过程中、留置期间、拔管或脱落期间均未观察到不良事件的发生。最 近一项关于全球 20 年间 FMT 相关不良反应的系统性综述 [33] 也显示,结肠 TET 是所有移植途径中不良事件发生率最低的途径。一项针对 224 例使用结肠 TET 的患者的观察性研究表明,TET 管在结肠内的中位保留时间为 8.5 天,这为 TET 管可用于重复移植提供了证据 [89] 。 一项研究调查了 3-7 岁儿童父母选择最愿意接 受的移植途径, 结果显示在接受结肠 TET 后, 父母对结肠 TET 的满意度为 100%, 且有 70.21%的父母首选结肠 TET 途径 [90] 。 TET 不仅可用于给药以及洗涤菌群的输入,还可以通过此管取样进行研究。 最近的一项研究 [91] 通过结肠 TET 采集人体原位的回盲部菌群样本,揭示肠道菌 群在泻药扰动后的固有恢复力,回肠菌群在组成和功能层面上的昼夜节律,以及 菌群通过代谢物对宿主的潜在影响。 结肠 TET 还可用于结肠减压。我们最近的研究首次报道 [92] ,利用结肠 TET 调节个体的肠道菌群以期获得更好的健康, 不应仅仅被视为一个技术或医学 问题,这些变化可能会影响个体甚至整个社会,因此,FMT 必须遵循相应的伦 理学原则 [93] 。当前,过度限制 FMT 和滥用 FMT 的问题在中国都同时存在。 尽管原始粗糙的"粪便移植"在 2011 年被统一为"粪菌移植",目的只是 引导认识这一技术的本质, 让人从根本上聚焦微生态的重要价值, 但并未改变 "粪 ...…”
Section: 上消化道途径 临床常见上消化道途径主要指口服粪菌胶囊及通过鼻胃管输注粪菌悬液。 上 消化道途径给药前必须 排除胃排空延迟...unclassified
“…Enema is an easy way of delivering fecal microbiota, but the access only arrives at the rectum and the sigmoid colon, making it difficult for children to hold the delivered microbiota for enough time. Therefore, in order to meet the needs of patients with multiple fresh WMTs or whole-colon administration of medications with one to two weeks, we developed a colonic delivery method for long-term maintenance of an indwelling, colonoscopically placed transanal enteral tube, which was called colonic transendoscopic enteral tubing (TET) [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method may be less psychologically challenging for patients than delivery of WMT via the upper and middle gut. The recent study reported that two to four large endoscopic clips could be recommended to maintain the TET tube within the colon for over 7 days in adults [ 18 ]. Our recent randomized controlled trial indicates that cap-assisted colonoscopy can reduce the time of second incubation of colonoscope in those colonoscopies with difficulty and decrease abdominal pain during endoscopy [ 25 ].…”
Section: Introductionmentioning
confidence: 99%